(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
The main aim of our study is to summarize briefly the process of the transition to the Bologna system in primary school and kindergarten teacher training; to outline the main streams of this change, the positive and negative sides and the experience gained after finishing the first training course.